Socioeconomic and Demographic Status and Perceived Health Risks of E-Cigarette Product Contents Among Youth: Results From a National Survey. Issue 1 (January 2020) - Vu, Thanh-Huyen T.; Groom, Allison; Hart, Joy L.; Tran, Hy; Landry, Robyn L.; Ma, Jennie Z.; Walker, Kandi L.; Giachello, Aida L.; Kesh, Anshula; Payne, Thomas J.; Robertson, Rose Marie
Background. The prevalence of e-cigarette use among youth is rising and may be associated with perceptions of health risks for these products. We examined how demographic factors and socioeconomic status (SES) are correlated with the perceived health risks of e-cigarette product contents among youth. Method . Data were from a national online survey of youth aged 13 to 18 between August and October 2017, weighted to be representative of the overall U.S. population in age, sex, race/ethnicity, and region. Survey analysis procedures were used. Results . Of 1, 549 e-cigarette users and 1, 451 never-e-cigarette users, 20.9% were Hispanic, 13.7% Black, 21.7% LGBTQ (lesbian/gay/bisexual/transgender/queer), and 49.3% in low-income families. With adjustment for e-cigarette use status, perceived health risks of nicotine and toxins/chemicals in e-cigarettes significantly differed by gender, race, sexual orientation, and SES ( p s < .05). For example, adjusted odds of perceiving harm from nicotine were 60% higher in girls versus boys, 34% lower in non-Hispanic Blacks versus non-Hispanic Whites, 33% lower in urban versus suburban residents, 40% higher in LGBTQ versus straight-identifying individuals, and 28% lower in low-income versus high-income families. Lower parental education level also was associated with children's lower health risk perception of e-cigarette product contents. Conclusions . For youth, the perceived health risks of e-cigarette product contents were associated with demographics, sexual orientation, and SES. The findings may have relevance for developing communication and education strategies addressing specific youth audiences, especially those in vulnerable groups. These strategies could improve awareness among youth concerning the health risks of e-cigarettes, helping to prevent or reduce e-cigarette uptake and continued use.